Three‐dimensional electro‐anatomical mapping and radiofrequency ablation as a novel treatment for atrioventricular accessory pathway in a horse: A case report. (3rd March 2023) - Buschmann, Eva; Van Steenkiste, Glenn; Boussy, Tim; Vernemmen, Ingrid; Schauvliege, Stijn; Decloedt, Annelies; van Loon, Gunther
Abstract: We describe the diagnosis and treatment of an atrioventricular accessory pathway (AP) in a horse using 3‐dimensional electro‐anatomical mapping (3D EAM) and radiofrequency catheter ablation (RFCA). During routine evaluation of the horse, intermittent ventricular pre‐excitation was identified on the ECG, characterized by a short PQ interval and abnormal QRS morphology. A right cranial location of the AP was suspected from the 12‐lead ECG and vectorcardiography. After precise localization of the AP using 3D EAM, ablation was performed and AP conduction was eliminated. Immediately after recovery from anesthesia an occasional pre‐excited complex still was observed, but a 24‐hour ECG and an ECG during exercise 1 and 6 weeks after the procedure showed complete disappearance of pre‐excitation. This case shows the feasibility of 3D EAM and RFCA to identify and treat an AP in horses.